(untitled) (Baghdad Science Journal, 2006)
Observed visually prominent lumps on the surface of the lung or embedded in lung tissue and microscopically Register Anfaj thrombosis with pulmonary carcinoma that took shape food or with the composition of the vesicles papillomavirus lining cells cubic vertical or connective tissue and increase